Pathogenesis of Anti-melanoma Differentiation-Associated Gene 5 Antibody-Positive Dermatomyositis: A Concise Review With an Emphasis on Type I Interferon System - Hu, Huifang; Yang, Hang; Liu, Yi; Yan, Bing (Frontiers in Medicine, 2022)
Anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis (MDA5+ DM) is typically characterized by cutaneous manifestations, amyopathic or hypomyopathic muscle involvement, and a high incidence of rapid progressive interstitial lung disease (RP-ILD). However, the exact etiology and pathogenesis of this condition has yet to be fully elucidated. Melanoma differentiation-associated gene 5 (MDA5), as the autoantigen target, is a member of the retinoic acid-inducible gene-I (RIG-I) family. The MDA5 protein can function as a cytosolic sensor that recognizes viral double-strand RNA and then triggers the transcription of genes encoding type I interferon (IFN). Therefore, it was presumed that viruses might trigger the overproduction of type I IFN, thus contributing to the development of MDA5+ DM. Emerging evidence provides further support to this hypothesis: the increased serum IFNα level was detected in the patients with MDA5+ DM, and the type I IFN gene signature was upregulated in both the peripheral blood mononuclear cells (PBMCs) and the skin tissues from these patients. In particular, RNA sequencing revealed the over-expression of the type I IFN genes in blood vessels from MDA5+ DM patients. In addition, Janus kinase (JAK) inhibitors achieved the promising therapeutic effects in cases with interstitial lung disease (ILD) associated with MDA5+ DM. In this review, we discuss the role of the type I IFN system in the pathogenesis of MDA5+ DM.